The effect of mind mapping assignment on creative thinking skills and biology concepts mastery in Senior High School - Azizurahmah, Annisyah; Sukarso, AA; Kusmiyati, Kusmiyati; Handayani, Sri (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
This study aims to ascertain how grade XI students at SMAN 8 Mataram's mind mapping assignment affects their capacity for original thought and their grasp of biological ideas. On samples chosen by random sampling, this study employed a pretest-posttest control group design and a quasi-experiment. While written assessments in multiple-choice questions were used to get information on topic mastery, mind-mapping assignments were used to gather information on students' creative thinking abilities. The findings demonstrated that mind-mapping exercises significantly impacted students' comprehension of biological topics and enhanced their capacity for creative thought, moving them from less creative to highly creative criteria. Pearson correlation test results showed a positive relationship between creative thinking skills and students' mastery of biological concepts in the medium correlation category. Mind mapping assignment has a positive influence in improving creative thinking skills and mastery of biological concepts of high school students, where students become more creative by simply connecting their prior knowledge with subsequent knowledge.